The Greek passion opera in 4 acts ; H 372/II (Zürich version 1957-9) = Řecké pašije - Martinů, Bohuslav 1890-1959 (Supraphon Music, 2007)
The tragic opera based on Nikos Kazantzakis's novel about a Small Greek village where the town's people re-enact the Passion of Christ
TV film from 1999. - Interpr.: John Mitchinson [Manolios]. Helen Field [Katerina]. John Tomlinson [Grigoris the Priest]. Jeffrey Lawton [Panait]. Artur Davies [Yannakos]. Geoffrey Moses [Foties the priest]. Rita Cullis [Lenio]. Philip Joll [Kostandis]. Catherine Savory [Nikolio]. John Harris [Michelis]. David Gwynne [Old man]. Jeffrey Lawton [Andonis]. Jana Jonásová [Despinio]. David Gwynne [Patriarcheas]. Michael Geliot [Ladas]. Prague Philharmonic Choir. Kühn Children's Choir. Brno Philharmonic Orchestra. Charles Mackerras [Dir.]. Tomáš Šimerda [Regie]- Englisch gesungen. - Aufn.: Brünn, Stadion Studio, 1. - 6. Juni 1981. - Engl. gesungen. - Untertitel: dt., engl., franz. und tschech.
Keywords: Operas; DVD-Video